Optimization of Palm Oil Production Efficiency Improvement Using Waste Assessment Model and Value Stream Analysis - Maizi, Hazful; Aflizal Zubir, Awal; Izzaty, Nur; Jariyah, Ainun; Raysan, M. Rafie (Jurnal Rekayasa Teknologi Nusa Putra, 2025)
PT XYZ is a company engaged in the processing of palm oil into Crude Palm Oil (CPO) and Palm Kernel Oil (PKO), operating in Berau, East Kalimantan. During the production process, there are efficiency-related issues. Therefore, this study aims to improve the efficiency of palm oil production by identifying value streams and waste using the Waste Assessment Model (WAM). The goal is to determine the most dominant waste type during CPO production and analyze the production process in detail using Value Stream Mapping (VSM). The VSM results reveal six workstations with a total of 15 operators, a lead time of 314 minutes, and value-added time of 174 minutes, resulting in a Process Cycle Efficiency (PCE) of 55,41% by applying the WAM method, waiting time emerges as the most dominant waste, accounting for 23,43%. Factors contributing to this waste include operator skill gaps, communication issues, and unexpected absences. Based on Process Activity Mapping (PAM), operational activities constitute the largest percentage (61,60%), with a value-added activity rate of 73.42%. Proposed improvements involve eliminating non-value-added activities, reducing the total lead time to 237 minutes, and increasing the PCE to 73.41%. These enhancements include implementing the 5S concept to minimize waste and enhance efficiency.